Crosstalk between regulated necrosis and micronutrition, bridged by reactive oxygen species - Zhang, Lei; Liu, Jinting; Dai, Ziyan; Wang, Jia; Wu, Mengyang; Su, Ruicong; Zhang, Di (Frontiers in Nutrition, 2022)
The discovery of regulated necrosis revitalizes the understanding of necrosis from a passive and accidental cell death to a highly coordinated and genetically regulated cell death routine. Since the emergence of RIPK1 (receptor-interacting protein kinase 1)-RIPK3-MLKL (mixed lineage kinase domain-like) axis-mediated necroptosis, various other forms of regulated necrosis, including ferroptosis and pyroptosis, have been described, which deepen the understanding of pathophysiological nature of diseases and provide novel therapeutics. Micronutrients, vitamins and minerals, position centrally in metabolism, which are required to maintain cellular homeostasis and functions. A steady supply of micronutrients benefits health, whereas either deficiency or excessive amount of micronutrients is considered harmful and clinically associated with certain diseases, such as cardiovascular disease and neurodegenerative disease. Recent evidence reveal that micronutrients are actively involved in the signaling pathways of regulated necrosis. For example, iron-mediated oxidative stress led to lipid peroxidation, which triggered ferroptotic cell death in cancer cells. In this review, we illustrate the crosstalk between micronutrients and regulated necrosis, and unravel the important roles of micronutrients in the process of regulated necrosis. Meanwhile, we analyze the perspective mechanism that each micronutrient contributes to regulated necrosis, with a particular focus on reactive oxygen species (ROS).